1986
DOI: 10.1002/etc.5620050703
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of halogenated benzene derivatives: Part VII. Photoincorporations of polychlorobenzenes with humic model monomers in aqueous acetonitrile solutions

Abstract: Aqueous acetonitrile solution‐phase photoincorporations of six polychlorobenzenes (PCBzs) into some humic model monomers such as benzoic acid, benzaldehyde, vanillic acid, vanillin, syringic acid and syringaldehyde were investigated using UV light centered at 300 nm. All the PCBzs studied except hexachlorobenzene yielded photoproducts by the reaction of the poly‐chlorophenyl radicals with the individual humic monomers. Chlorophenylation of humic model monomers occurred in the case of benzoic acid and benzaldeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…16 Likewise, the irradiation of solution of T 4 CBz 77 in wateracetonitrile (1:1 v/v) containing vanillic acid (12) yielded, in addition to other photoincorporated products 13, monochloro-(75) and dichloromethoxycarbohydroxydibenzofuran (14) (Reaction 8). 15 It was concluded that these PCDFs are formed through the intermediacy of appropriate polychlorodiphenyl ethers (PCDEs) which undergo secondary photochemical reactions to produce the final products. 15 ' 16…”
Section: %mentioning
confidence: 99%
“…16 Likewise, the irradiation of solution of T 4 CBz 77 in wateracetonitrile (1:1 v/v) containing vanillic acid (12) yielded, in addition to other photoincorporated products 13, monochloro-(75) and dichloromethoxycarbohydroxydibenzofuran (14) (Reaction 8). 15 It was concluded that these PCDFs are formed through the intermediacy of appropriate polychlorodiphenyl ethers (PCDEs) which undergo secondary photochemical reactions to produce the final products. 15 ' 16…”
Section: %mentioning
confidence: 99%
“…Recently, we (22) have reported our investigations on the environmental photochemistry of several PCPs, namely tetra-and pentachlorophenols in H20-CH3CN (2:3 v/v) at A r 290 nm concluding that the process of reductive 'For Part VII, see ref. 1. 2~o whom all correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…1; and the preceding articles of this series cited therein), we decided to further investigate the photochemistry of 1 dissolved in water-acetonitrile (2:3 v/v) at A 2 290 nm. This paper presents the structural elucidation of the photoproduct C8H3C14N0 (2) arising from pentachlorophenol (1) in aqueous acetonitrile along with the proposed mechanisms for the formation and mass fragmentation pattern of compound 2.…”
Section: Introductionmentioning
confidence: 99%
“…Well-known examples are the highly toxic polychlorinated dioxins (PCDDs) and dibenzofuranes (PCDFs) formed in municipal incinerators. In this context chlorobenzene is known to be an important precursor for PCDDs and PCDFs (17)(18)(19).…”
mentioning
confidence: 99%